A luteinizing hormone-releasing hormone agonist decreases biological activity and modifies chromatographic behavior of luteinizing hormone in man. - Evans, R M (1984)
The effect of the luteinizing hormone-releasing hormone (LHRH) agonist, [D-Trp6,Pro9-NEth]LHRH (LHRHA), on luteinizing hormone (LH) bioactivity was assessed with a rat interstitial cell assay in four men during a 14-d treatment period. Biologic/immunologic (B/I) ratios were unchanged initially with treatment but by day 12 had fallen to levels lower than basal values. Frequent sampling on day 12 revealed blunted gonadotropin responsiveness to LHRHA and absence of spontaneous LH pulsations. Despite continued administration of LHRHA, human chorionic gonadotropin administration resulted in elevated B/I ratios and testosterone levels. Further characterization of the serum immunoreactive LH by Sephadex chromatography revealed a later elution profile during treatment with LHRHA. Thus, LHRHA appears to act, in part, by modification of the bioactivity of LH in man.